Análise de cenários para a indústria postal brasileira: um estudo sobre a adequação da distribuição domiciliária às tendências do mercado - Aguiar, Fernanda Rocha de (Universidade do Vale do Rio dos Sinos, 2018)
This paper aims to analyze the possible scenarios of the Brazilian postal industry in a horizon up to 2028, from the economic, social, political, technological and legal effects resulting from the transformations of this market. It is a fact that companies are using digital channels to issue accounts, statements and invoices. People now use social networks and smartphones to communicate with family and friends. In addition, consumers are gradually shifting from physical stores to shopping online. In other words, both the substitution of physical correspondence by means of e-commerce and e-commerce are on the rise and result in challenges and opportunities for the postal industry, as well as boosting efforts to diversify and increase efficiency and innovation. These considerations motivated the development of a qualitative research of an exploratory nature using the Scenario Analysis method from information provided by Brazilian mail specialists as well as actors from the contextual environment in which the company is inserted. The research was performed through semi-structured interviews in which the information was cleared through Content Analysis. As a result, four scenarios were built based on the uncertainties and trends of the Brazilian postal industry in order to indicate how home delivery may be appropriate to these perspectives. From the analysis of the scenarios, validated by specialists, it is emphasized that Brazilian postal industry needs strategies that can prepare the organization to cross the different situations that were designed, especially with the need to diversify its business model, including product remodeling, flexibility in their activities and innovation of their platforms. Otherwise, the company could be directed to the reality of the precariousness of the services that represents the poor quality and lack of operational efficiency, forcing the premises of privatization or end of the postal monopoly for Brazilian postal service.
Keywords: Distribuição domiciliária; Análise de cenários; Indústria postal; Home deliveries; Scenario analysis; Postal industry; ACCNPQ::Ciências Sociais Aplicadas::Administração